ANÁLISE DOS GOLS EM JOGOS DE FUTSAL SUB-17 NO CAMPEONATO ESTADUAL DE SÃO PAULO 2012 - Jussiê de Melo de Campos (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2014)
Introduction: Currently, futsal is a unpredictable game and there are several possibilities of goals. Objective: The objective of this study was to analyze how the goals occurred in the games of the São Paulo championship 2012. Materials and methods: Were analyzed technical tactical actions. The sample consisted of shooting 6 of 10 first rounds matches of the 2012 state team. Data were recorded in Excel 2007. The method adopted was quantitative. Results and Discussion: In the results the technical-tactical actions that stood out over the others were the moves combined and individual plays with 40% and 23% respectively. The moves set pieces resulted in 20%, representing a substantial number of total goals in the games studied. Conclusion: It can be concluded that there is an advantage in goals in the context of technical-tactical Combined Played and played-pieces were also significant in the research.